Spiritual well-being in the 21st century: It is time to review the current WHO’s health definition - Francesco Chirico (Journal of Health and Social Sciences)
Over the years, some critics argue that the dimension of spiritual well-being was missing from the World Health Organization’s (WHO) definition of health. Nevertheless, although the WHO’s definition has been criticized over the past 60 years, it has never been adapted. Spiritual well-being should not be confused with psychological well-being. Moreover, spirituality, personal beliefs and religiousness are not synonymous. Spirituality has received much interest in health care services; it can improve strategies for managing stress and can positively influence immune, cardiovascular (heart and blood vessels), hormonal, and nervous systems. For this reason, it may be implicated in a wide range of physical and mental health conditions, and I believe it’s time to review the WHO’s health definition, adding to it the ‘spiritual well-being’ dimension.